Kebijakan Moneter Dalam Pemulihan Ekonomi Indonesia Pada Masa Pandemi Covid-19 - Saputro, M. Veri Galih Nugroho; Fakhri, Miftahul Ghulam Al (Journal of Economics and Social Sciences (JESS), 2024)
Introduction/Main Objectives: The Covid-19 pandemic, including Indonesia, has disrupted the world economy. In the world, Covid-19 has eroded the economy by USD 8.8 trillion or 9.7%. Bank Indonesia, the central bank that regulates monetary policy, has restored the economic problems that have occurred by collaborating with the government. This study aims to determine monetary policy in economic recovery during the Covid-19 pandemic. Research Methods: The method used in this research is qualitative with literature study techniques sourced from articles, books, journals, or other related sources. Finding/Results: The results of this study indicate that the monetary policies implemented by Bank Indonesia include accommodative macroprudential policies, rupiah exchange rate stability policies, SBN purchase policies from the secondary market, policy interest rate reductions (BI7DRR), and social assistance distribution policies (bansos) with the government. Conclusion: From several policies, it can be concluded that Bank Indonesia is serious in dealing with economic problems during the Covid-19 pandemic. So it is hoped that with the right Monetary Policy, the economy in Indonesia will improve.